A Web of Intercultural Communication - Papadima-Sophocleous, Salomi (My University, 2003)
The world today is characterized by an ever-growing number of contacts resulting in communication between people with different linguistic and cultural backgrounds, experiences and practices. On the one hand, many societies are becoming more and more multicultural, and on the other many people and organizations collaborate across geographic and cultural boundaries. In all these contacts it is important for communication to be as constructive as possible, without misunderstandings and breakdowns. New communication technology (e.g. email and the WWW) has made it easier to a certain extent to cross previous boundaries and communicate across time and space. However, the new technology puts us in front of new challenges in order to effectively collaborate and communicate interculturally. Cyber printed information has an important role to play in intercultural communication. This paper defines the concepts of inter, culture, communication and the web, thus setting a basis for discussion towards improvement' of intercultural communication in cyberspace. Through some examples of intercultural misunderstanding the paper identifies some of the aspects that cause cultural misunderstanding on the web and suggests ways in which we can work towards a Web of Intercultural Communication.
Keywords: Intercultural communication; Web; New Technologies